2002
DOI: 10.1103/physrevlett.88.113901
|View full text |Cite
|
Sign up to set email alerts
|

Honeycomb Pattern Formation by Laser-Beam Filamentation in Atomic Sodium Vapor

Abstract: We have observed transverse pattern formation leading to highly regular structures in both the near and far fields when a near-resonant laser beam propagates without feedback through an atomic sodium vapor. One example is a regular far-field honeycomb pattern, which results from the transformation of the laser beam within the vapor into a stable three-lobed structure with a uniform phase distribution and highly correlated power fluctuations. The predictions of a theoretical model of the filamentation process a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
19
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(19 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…This regime valid for larger optical thickness will be considered in this letter. Note that in contrast to past observation of pattern formation in hot atomic vapors [19,20] the instabilities based on the coupling to the atomic motion do not require non linear optical response of the atoms.…”
mentioning
confidence: 81%
“…This regime valid for larger optical thickness will be considered in this letter. Note that in contrast to past observation of pattern formation in hot atomic vapors [19,20] the instabilities based on the coupling to the atomic motion do not require non linear optical response of the atoms.…”
mentioning
confidence: 81%
“…1, in which, large detuning of the pump 1 and the pump 2 is needed for high conversion efficiency. The noise is mainly from pump 2 field due to the pattern formation with high power [15]. It is worth illustrating that the polarization of the pump fields and signal field affect obviously the efficiency of conversion.…”
mentioning
confidence: 99%
“…It has been reported that the atomic coherence can significantly enhance and modify the cross-Kerr nonlinearities [1,3], which are essential in generating large refractive index modulation [4]. With the nonlinear refractive index changed, laser induced focusing [5] and pattern formation [6] have been extensively investigated with two laser beams propagating in atomic vapors.…”
Section: Introductionmentioning
confidence: 99%